2015
DOI: 10.1111/apt.13492
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta-analysis: long-term outcomes of faecal microbiota transplantation forClostridium difficileinfection

Abstract: Summary Background Clostridium difficile infection is a major cause of nosocomial diarrhoea. Aim To evaluate long‐term (≥90 days) efficacy and safety of faecal microbiota transplantation for C. difficile infection and explore the factors affecting the faecal microbiota transplantation outcomes. Methods MEDLINE, the Cochrane Library and EMBASE were searched and only observational studies that utilised faecal microbiota transplantation for C. difficile infection with long‐term follow‐up duration (≥90 days) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 57 publications
(259 reference statements)
5
88
0
7
Order By: Relevance
“…The cure rate in our FMT-treated patients was 94%. Our data are conform to the results obtained in previous studies (12). In one patient with severe, pseudomembranous, therapyrefractory CDI the application of FMT failed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The cure rate in our FMT-treated patients was 94%. Our data are conform to the results obtained in previous studies (12). In one patient with severe, pseudomembranous, therapyrefractory CDI the application of FMT failed.…”
Section: Discussionsupporting
confidence: 92%
“…The first very promising, placebo-controlled trial by Van Nood et al, confirmed the high effectivity of this method in the treatment of CDI (11). Further meta-analyses demonstrated a cure rate of over 90% in CDI patients treated with FMT (12). The effectiveness of FMT in patients with CDI provides important proof of concept that dysbiotic gut microbiota can be restored by transplantation of microbiota from a healthy donor.…”
mentioning
confidence: 93%
“…In spite of this, a recent systematic and meta-analysis indicates that adverse events after fecal microbiota transplantation such as autoimmune disease and infectious disease was not significant in a follow up of 90 d after transplantation, whereas authors identified old age of patients (>65 years) as a risk factor for the primary cure failure and early recurrence. 46 Beyond this, it should be possible to isolate a fecal cocktail of defined bacterial multi-species and/or design synthetic mixtures that could be administered for correcting intestinal dysbiosis, thus avoiding the risk of transmission of potentially harmful microorganisms from donors to recipients. 47 …”
Section: The Gut Microbiome: Composition Functionality and Evolutionmentioning
confidence: 99%
“…Our group has previously demonstrated that bowel preparation and colonoscopy does not change the microbiota in most subjects, 30 but noted that three patients suffering from ulcerative colitis did not have restoration of their pre-colonoscopy microbiome. Therapeutic manipulation of the microbiome, for example with faecal microbial transplantation, has had mixed results in IBD cohorts compared to those with recurrent Clostridium difficile colitis, 31 , 32 also raising the possibility that there is instability of the microbiome in IBD patients compared to previously healthy subjects.…”
Section: Discussionmentioning
confidence: 99%